System Oriented Sustainable Supply Chain Management Innovations in Automotive Industry – Skoda Auto Case Study - Cee, Jiri; Dieiev, Oleksii; Holman, David; Lenort, Radim; Stas, David; Wicher, Pavel (Communications - Scientific letters of the University of Zilina, 2016)
System thinking and system theory are currently widely used in a variety of subjects and fields. Sustainability Supply Chain Management is defined as the strategic, transparent integration and achievement of an organization’s social, environmental, and economic goals. The automotive industry is known as one of the most competitive branches in the industrial sphere. Efficient and effective deliveries of complete cars are fundamentally dependent on the performance of the delivery concept in the whole supply chain. The aim of the article is to research and define the fundamental principles and assumptions of system oriented innovations utilized in the Sustainable Supply Chain Management of automotive industry. These principles are derived on the basis of the case study related to the Efficient, Electronic, and Ecology Delivery Concept developed by SKODA AUTO Logistics.